Controle da 'lagarta do cartucho do milho', Spodoptera frugiperda, pelo carbaril, carbofuram, dipel (Bacillus thuringiensis) e endossulfam - Gomes de Lima, José Oscar; Cola Zanuncio, José (Revista Ceres, 2025)
Five inseticides formulations were compared for effectiveness against the fall armyworm on maize at Vigosa, Minas Gerais. Tests were conducted on 17 and 21 December 1974. A plot consisted of a row of maize 20 m in length, about 100 plants 0.6 m high, heavily infested by larvae about 20 ram long. Each plot was replicated 5 times. Carbaryl WP applied at the rate of 1.0 kg AI/ha, and Carbofuran G and WP, Endossulfan EC, and Dipel (Bacillus thuringiensis) WP at 0.5 kg Al/ha. Water was used at the equivalent of 500 1/ha. Granular insecticide was applied by hand and the others with a knapsack sprayer with a fan nozzle. Mortality was recorded 48 hours after application. Except for Dipel which was unsatisfactory, all insecticides gave similar results. Mortality was over 76% in both tests Endosulfan was slightly phytotoxic to the crop.